2020
DOI: 10.2147/ijn.s259993
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Non-Lipolysis Nanoemulsion Improved Oral Bioavailability by Reducing the First-Pass Metabolism of Raloxifene, and Related Absorption Mechanisms Being Studied</p>

Abstract: A non-lipolysis nanoemulsion (NNE) was designed to reduce the first-pass metabolism of raloxifene (RAL) by intestinal UDP-glucuronosyltransferases (UGTs) for increasing the oral absorption of RAL, coupled with in vitro and in vivo studies. Methods: In vitro stability of NNE was evaluated by lipolysis and the UGT metabolism system. The oral bioavailability of NNE was studied in rats and pigs. Finally, the absorption mechanisms of NNE were investigated by in situ single-pass intestinal perfusion (SPIP) in rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In this regard, Ye et al developed lipid nanoparticles (LNPs) as LDDS to increase raloxifene bioavailability through LS (Ye et al 2020 ). Similarly, Rangaraj et al prepared nanoscaled lipids materials as LDDS to enhance the bioavailability of Ibrutinib through the LS channel.…”
Section: Biomedical Applications Of Lddmentioning
confidence: 99%
“…In this regard, Ye et al developed lipid nanoparticles (LNPs) as LDDS to increase raloxifene bioavailability through LS (Ye et al 2020 ). Similarly, Rangaraj et al prepared nanoscaled lipids materials as LDDS to enhance the bioavailability of Ibrutinib through the LS channel.…”
Section: Biomedical Applications Of Lddmentioning
confidence: 99%
“…One plausible factor responsible for the large intersubject %CV for the FDC formulation could be the formulation complexities. The aqueous solubility of raloxifene is poor [ 5 ]. Mitra et al [ 19 ] reported that dissolution from the FDC formulation could slow down if high drug loading is required owing to restrictions on its final size [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This drug reduces bone resorption and turnover, leading to increased bone mineral density. Raloxifene is used as a first-line drug to treat and prevent osteoporosis in postmenopausal women [ 5 ]. In 3,204 postmenopausal women with osteopenia or osteoporosis, raloxifene 60 mg administered once daily for 3 years significantly decreased the risk of new vertebral fractures compared to that in the placebo group [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The harsh gastrointestinal environment owing to secretion of gastric acid, various surfactants and enzymes tends to degrade or inactivate certain labile entities including both small molecular drugs and biomacromolecules 9 , 10 , 11 , 12 . Some therapeutic compounds are stable and absorbable in the GIT, but are susceptible to first-pass hepatic metabolism and suffer from extremely low bioavailability 13 , 14 . Moreover, the enteric epithelia may also present as a formidable barrier to the entry of entities of less favorable properties 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%